Does soft really matter? Differentiation of induced pluripotent stem cells into mesenchymal stromal cells is not influenced by soft hydrogels. (February 2018) - Goetzke, Roman; Franzen, Julia; Ostrowska, Alina; Vogt, Michael; Blaeser, Andreas; Klein, Gerd; Rath, Björn; Fischer, Horst; Zenke, Martin; Wagner, Wolfgang
Abstract: Induced pluripotent stem cells (iPSCs) can be differentiated toward mesenchymal stromal cells (MSCs), but this transition remains incomplete. It has been suggested that matrix elasticity directs cell-fate decisions. Therefore, we followed the hypothesis that differentiation of primary MSCs and generation of iPSC-derived MSCs (iMSCs) is supported by a soft matrix of human platelet lysate (hPL-gel). We demonstrate that this fibrin-based hydrogel supports growth of primary MSCs with pronounced deposition of extracellular matrix, albeit it hardly impacts on gene expression profiles or in vitro differentiation of MSCs. Furthermore, iPSCs can be effectively differentiated toward MSC-like cells on the hydrogel. Unexpectedly, this complex differentiation process is not affected by the substrate: iMSCs generated on tissue culture plastic (TCP) or hPL-gel have the same morphology, immunophenotype, differentiation potential, and gene expression profiles. Moreover, global DNA methylation patterns are essentially identical in iMSCs generated on TCP or hPL-gel, indicating that they are epigenetically alike. Taken together, hPL-gel provides a powerful matrix that supports growth and differentiation of primary MSCs and iMSCs – but this soft hydrogel does not impact on lineage-specific differentiation.